2009
DOI: 10.1136/ard.2008.096487
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking as a risk factor for developing rheumatoid arthritis: a meta-analysis of observational studies

Abstract: Smoking is a risk factor for RA, especially RF+ RA men and heavy smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
384
3
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 544 publications
(430 citation statements)
references
References 57 publications
19
384
3
8
Order By: Relevance
“…Researchers found that in rheumatoid-factor-positive RA men, heavy smoking was a significant risk factor for RA: odds ratio 3.91, 95% CI 2.78 -5.50. 26 Specific studies on the association of RA-BR with smoking are lacking, but in fact the limited data available suggest that patients with RA-BR are more likely to be non-smokers, compared to those with RA alone. 15,27,28 Thus, from the available literature there is no evidence to implicate smoking in the association of RA and BR.…”
Section: Risk Factors Smokingmentioning
confidence: 99%
“…Researchers found that in rheumatoid-factor-positive RA men, heavy smoking was a significant risk factor for RA: odds ratio 3.91, 95% CI 2.78 -5.50. 26 Specific studies on the association of RA-BR with smoking are lacking, but in fact the limited data available suggest that patients with RA-BR are more likely to be non-smokers, compared to those with RA alone. 15,27,28 Thus, from the available literature there is no evidence to implicate smoking in the association of RA and BR.…”
Section: Risk Factors Smokingmentioning
confidence: 99%
“…Furthermore, in a meta-analysis of 16 studies on patients that smoked, it was identified that male smokers exhibited a summary OR of 1.87 (95% CI, 1.49-2.34) for developing RA and a summary OR of 3.91 (95% CI, 2.78-5.50) for positive rheumatoid factor. Furthermore, the same meta-analysis demonstrated that female smokers had respective OR values of 1.31 (95% CI, 1.12-1.54) and 1.29 (95% CI, 0.94-1.77) (40). Thus, smoking was a greater risk factor for developing RA in males compared with females, illustrating another similarity between Chikungunya fever and RA.…”
Section: Discussionmentioning
confidence: 74%
“…Cigarette smoking is recognized as an important risk factor for RA development and is associated with increased risk of comorbidities that are leading causes of death in RA, including cardiovascular and respiratory diseases (5)(6)(7)(8)(9)(10). Smoking cessation at any time after RA diagnosis was associated with decreased mortality risk in a recent large study in the UK (11).…”
Section: Introductionmentioning
confidence: 98%